2019
DOI: 10.1001/jamapediatrics.2019.0644
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Implications of Rising Marijuana Use in Pregnancy in an Age of Increasing Legalization

Abstract: mothers living in a lower-risk home environment. 1 This indicates that the differences in heritability estimates cannot be entirely explained by the differences in parental education. In addition, parental educational level is not a feasible modifiable target for public health interventions; rather, the specific environmental exposures captured in the home environment measure (eg, food availability in the home) need to be targeted. Therefore, in our view, parental education cannot be used as a proxy measure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, recent research suggests that regular use of cannabis in men causes epigenetic changes in sperm cells [23], and paternal cannabis use during pregnancy has, potentially, further epigenetic effects [24]. Studying effects of paternal cannabis use during pregnancy is encouraged [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research suggests that regular use of cannabis in men causes epigenetic changes in sperm cells [23], and paternal cannabis use during pregnancy has, potentially, further epigenetic effects [24]. Studying effects of paternal cannabis use during pregnancy is encouraged [25].…”
Section: Introductionmentioning
confidence: 99%
“…Marijuana and traditional cigarette use occur in up to 21% of young adults [17]. In contrast to alcohol and combustible tobacco consumption, marijuana use is increasing among pregnant women coincident with state-based legalization [18,19]. Rates of marijuana use may be further underestimated based on self-report alone as Young-Wolff et al [20] found that prevalence of marijuana use during pregnancy was higher based on toxicology than by patient recall [20].…”
Section: Introductionmentioning
confidence: 99%